The influence of competence and motivation on the work productivity of administrative staff at public senior high schools - Ilna, Ilna; Achyar, Novriyanti; Syahril, Syahril; Irsyad , Irsyad (Universitas Jambi, Indonesia, 2026)
This study aims to analyze the influence of competence and motivation on the work productivity of administrative staff at public senior high schools in Karimun Regency, Riau Islands Province. The study was motivated by the important role of administrative staff in supporting school services and management. However, their contribution often receives less attention compared to that of the teaching staff. This research employed a quantitative approach using a survey method involving 114 administrative staff from 14 public senior high schools in Karimun Regency. Data were collected through questionnaires that had been tested for validity and reliability, and were analyzed using multiple linear regression. The findings revealed that competence and motivation have a positive and significant effect on work productivity. Competence helps staff complete tasks more effectively, while motivation increases work engagement and responsibility. These findings highlight the importance of continuous training programs and managerial support in improving the quality of human resources within the school environment.